Chronic Kidney Disease and Fibrosis: The Role of Uremic Retention Solutes - Mutsaers, Henricus A. M.; Stribos, Elisabeth G. D.; Glorieux, Griet; Vanholder, Raymond; Olinga, Peter (Frontiers in Medicine, 2015)
Chronic kidney disease (CKD) is a major global health concern, and the uremic state is highly associated with fibrogenesis in several organs and tissues. Fibrosis is characterized by excessive production and deposition of extracellular matrix proteins with a detrimental impact on organ function. Another key feature of CKD is the retention and subsequent accumulation of solutes that are normally cleared by the healthy kidney. Several of these uremic retention solutes, including indoxyl sulfate and p-cresyl sulfate, have been suggested to be CKD-specific triggers for the development and perpetuation of fibrosis. The purpose of this brief review is to gather and discuss the current body of evidence linking uremic retention solutes to the fibrotic response during CKD, with a special emphasis on the pathophysiological mechanisms in the kidney.